Digital twin enabled sustainable urban road planning. (March 2022) - Jiang, Feng; Ma, Ling; Broyd, Tim; Chen, Weiya; Luo, Hanbin
Highlights: A DT-MCDM-GIS framework is proposed for sustainable urban road planning. Building demolition and land use are digitalized for urban road planning using digital twin. Traffic congestion and driving route selection habits are considered for urban road planning. The urban road planning considers the air quality and noise. The proposed approach considers both new road construction and existing old road widening. Abstract: Sustainable urban road planning should endeavor to meet current and future traffic-related demands and achieve financial, environmental, and social benefits, which is a complex and interdisciplinary issue that needs to consider various factors and data. Multi-criteria decision making (MCDM) can provide reasonable solutions, and some existing studies integrated MCDM with geographic information system (GIS) technology. This paper presents an urban road planning approach based on digital twin (DT), MCDM, and GIS called DT-MCDM-GIS framework. DT can digitalize the physical world to provide various data for the whole process; MCDM can provide criteria and evaluation methods; GIS can provide an integrated environment for analysis. Building demolition and land use, traffic congestion, driving route selection habits, air quality, and noise are all considered in the framework for urban road planning. The proposed approach can provide a functional, economic, people-friendly, eco-friendly urban road planning scheme considering new road construction and existing old road widening to alleviate traffic congestion and provide an alternative route for drivers that conforms to their habits.